2020
DOI: 10.1111/hae.13948
|View full text |Cite
|
Sign up to set email alerts
|

Genetic screening of children with suspected inherited bleeding disorders

Abstract: Introduction Genetic screening using high‐throughput DNA sequencing has become a tool in diagnosing patients with suspected inherited bleeding disorders (IBD). However, its usefulness and diagnostic efficacy in children is unclear. Aim To evaluate the diagnostic efficacy of genetic screening for IBD in children and downstream further testing. Methods After informed consent, children (<18 years) with suspected IBD underwent genetic screening with 94 selected genes. Results A total of 68 heterozygous class 3‐5 v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 37 publications
(80 reference statements)
0
15
0
Order By: Relevance
“…Different HTS studies for diagnostics of BPD have been published but for this review, we have only focussed on the studies that have used the guidelines for variant classification as formulated by the American College of Medical Genetics (ACMG) in 2015 [10]. Figure 2 provides an overview of the diagnostic rates obtained in these studies that however differ in terms of used HTS methods (TS or WES), studied pathologies (platelet disorders, coagulation disorders and bleeding of unknown etiology) and the number of genes and patients included [11][12][13][14][15][16][17][18][19][20][21]. In addition, these studies have used different inclusion criteria ranging from the selection of only patients with a known or suspected etiology (studies with typically high diagnostic rates) to patients with bleeding of unknown etiology and normal laboratory parameters (studies with very low diagnostic rates).…”
Section: Hts Technologies Used For Bpd Diagnosticsmentioning
confidence: 99%
See 4 more Smart Citations
“…Different HTS studies for diagnostics of BPD have been published but for this review, we have only focussed on the studies that have used the guidelines for variant classification as formulated by the American College of Medical Genetics (ACMG) in 2015 [10]. Figure 2 provides an overview of the diagnostic rates obtained in these studies that however differ in terms of used HTS methods (TS or WES), studied pathologies (platelet disorders, coagulation disorders and bleeding of unknown etiology) and the number of genes and patients included [11][12][13][14][15][16][17][18][19][20][21]. In addition, these studies have used different inclusion criteria ranging from the selection of only patients with a known or suspected etiology (studies with typically high diagnostic rates) to patients with bleeding of unknown etiology and normal laboratory parameters (studies with very low diagnostic rates).…”
Section: Hts Technologies Used For Bpd Diagnosticsmentioning
confidence: 99%
“…Other HTS studies have also reported variants in more than one gene but without further specifications if these had a clinical impact for the patient or family [11,[14][15][16][17][18]20]. Such examples of mostly digenic inheritance have recently also been documented in case reports.…”
Section: Accepted Articlementioning
confidence: 99%
See 3 more Smart Citations